Mental models and the mind : current developments in cognitive psychology, neuroscience, and philosophy of mind - Held, Carsten; Knauff, Markus; Vosgerau, Gottfried (Advances in psychology (Amsterdam, Netherlands), 2006)
Cognitive psychologists report their research on the representation and processing of mental models in human memory. Cognitive neuroscienctists demonstrate how visual and spatial mental models are processed in the brain. Philosophers discuss the role of mental models in relation to perception, emotion and intentionality.